Eco-friendly, selective hydroxylation of C-7 aromatic compounds catalyzed by TS-1/H2O2 system under solvent-free solid-liquid-liquid-type triphase conditions - Mukherjee, P.; Bhaumik, Asim; Kumar, Rajiv (Industrial & Engineering Chemistry Research, 2007)
Direct ring hydroxylation of aromatics, namely, anisole, toluene, and benzylchloride, using TS-1 catalyst, a MFI-type titanium silicate molecular sieve, dilute H2O2 as oxidizing agent, and water as reaction medium, was investigated under solid-liquid-liquid (SLL)-type triphase conditions. The aim was to study the relative influence of commonly used organic solvents, under solid-liquid (SL)-type biphase reaction conditions, as compared to that of water, on the conversion and product selectivity. Under solvent-free triphase conditions, the ring hydroxylation of anisole, toluene, and benzylchloride leads to significant enhancement in the conversion, turn-over frequency, and para-selectivity. However, in the case of benzyl chloride, no ring hydroxylation took place under biphase conditions (using acetone as solvent) contrary to significant ring hydroxylation (ca. 60% H2O2 efficiency) under triphase aqueous medium conditions. The simple product recovery (phase separation of organic and aqueous layers) and use of water as reaction medium are other advantages. Since TS-1 is relatively hydrophobic, the reaction is hindered in the presence of organic solvents as they compete favorably with the substrate for diffusion inside the TS-1 channels. However, in the presence of water, the organic substrate competes favorably with water, leading to increased conversion and para-selectivity.